PENGARUH MEDIA GAMBAR TERHADAP PROSES DAN HASIL BELAJAR SISWA SEKOLAH DASAR: STUDI PUSTAKA - Ilham (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The quality of learning processes and outcomes of elementary school students is often constrained by the use of conventional teaching methods that are not supported by appropriate learning media. Considerg that elementary school students are at the concrete operational stage, visual learning media are essential to facilitate meaningful learning. This study aims to review the influence of pictorial media on the learning process and learning outcomes of elementary school students. The research employed a library research method with a descriptive qualitative approach. Data were collected from nationally accredited SINTA journal articles relevant to the use of pictorial media in elementary school learning. Documentation techniques were used to select articles based on relevance and completeness. The data were analyzed by identifying research objectives, methods, and findings, followed by systematic synthesis. The results indicate that pictorial media positively influence learning processes, including increased learning interest, student engagement, and understanding. In addition, pictorial media contribute to improved learning outcomes, particularly in early reading skills, reading comprehension, and writing abilities. Therefore, pictorial media are effective instructional tools for improving the quality of elementary school learning